Inactivation of chikungunya virus in blood components treated with amotosalen/ultraviolet A light or amustaline/glutathione. Issue 3 (10th January 2018) - Laughhunn, Andrew; Huang, Yan‐Jang S.; Vanlandingham, Dana L.; Lanteri, Marion C.; Stassinopoulos, Adonis
Abstract : BACKGROUND: Chikungunya virus, a mosquito‐borne arbovirus, often co‐circulates with the Zika, dengue, and yellow fever viruses in Aedes mosquito‐infested areas where cases of arbovirus transfusion‐transmitted infections have been reported. Building on past experience to help maintain the availability of safe components during major outbreaks of chikungunya virus in La Reunion, Italy, and Thailand and of Zika virus in the Pacific, the Caribbean, and the Americas, pathogen inactivation is a mitigation strategy to reduce the risk of transfusion‐transmitted infection. Inactivation of chikungunya virus was investigated for platelets in 100% plasma using amotosalen/ultraviolet A light, and in red blood cells using amustaline/glutathione. STUDY DESIGN AND METHODS: Platelets in 100% plasma and red blood cells (RBCs) were spiked with chikungunya virus. Infectious chikungunya virus titers were measured in contaminated blood products before and after treatment with amotosalen/ultraviolet A light for platelets in 100% plasma and after treatment with amustaline/glutathione for RBCs. Viral infectivity was quantified by plaque assay. RESULTS: The mean chikungunya virus infectivity titers before inactivation were 6.50 log10 plaque‐forming units/mL for platelets in 100% plasma and 7.60 log10 plaque‐forming units/mL for RBCs. No infectivity was detected after amotosalen/ultraviolet A light or amustaline/glutathione treatment, corresponding to greater than 6.5 log10 plaque‐forming units/mL and greater than 7.1 log10 plaque‐forming units/mL of inactivation, respectively. CONCLUSION: Robust levels of chikungunya virus inactivation were achieved for platelets in 100% plasma and for RBC components. The licensed amotosalen/ultraviolet A light technology and the amustaline/glutathione pathogen‐reduction system under development may provide an opportunity for comprehensive mitigation of the risk of chikungunya virus transfusion‐transmitted infection by plasma, platelets, and RBCs.